Quantification of the water balance and hydrogeological processes of groundwater-lake interactions in the Pampa Plain, Argentina - Bocanegra, E. (2013)
This paper gives an account of the assessment and quantification of the water balance and the hydrogeological processes related to lake–groundwater interaction in the Pampa Plain by using hydrogeochemical, isotopic and flow numerical modeling techniques. La Salada is a permanent shallow lake, with an area of 5.8 km2, located on the SE of Buenos Aires Province. A total of 29 lake water samples and 15 groundwater samples were collected for both hydrochemical analysis and environmental stable isotope determination. Water table depths were measured in wells closed to the lake. Groundwater samples appear grouped on the Local Meteoric Water Line, suggesting a well-mixed system and that rainfall is the main recharge source to the aquifer. Water evaporation process within La Salada is also corroborated by its isotopic composition. The model that best adjusts to La Salada Lake hydrochemical processes includes evaporation from groundwater, calcite precipitation with CO2 release and cationic exchange. The annual water balance terms for the lake basin indicates for each hydrological component the following values: 1.16 E08 m3 rainfall, 8.15 E07 m3 evapotranspiration, 1.90 E06 m3 runoff, 1.55 E07 m3 groundwater recharge, 6.01 E06 m3 groundwater discharge to the lake, 9.54 E06 m3 groundwater discharge to the river, 5.00 E05 m3 urban extraction and 4.90 E06 m3 lake evaporation. Integrated analysis of hydrochemical and isotopic information helped to calibrate the groundwater flow model, to validate the conceptual model and to quantitatively assess the basin water balance.